A novel approach for dynamic compaction of Mg–SiC nanocomposite powder using a modified Split Hopkinson Pressure Bar. (15th March 2018) - Rahmani, K.; Majzoobi, G. H.; Atrian, A.
ABSTRACT: In this paper, fabrication and characterisation of Mg–SiC nanocomposite are investigated. Micrometre-sized Mg powder with the different volume fraction of SiC nano particles were dynamically compacted using a modified Split Hopkinson Pressure Bar. Moreover, the compaction process was simulated using AUTODYN commercial software to demonstrate that the stress in the powder sample was sufficient for consolidation. To achieve the best quality samples, the effects of lubrication and compaction velocity on dynamic compaction process were initially studied by experiment. It was observed that the temperature of 450°C and the compaction velocity of 15.5 m/s led to the best samples with relative density more than 99%. The effects of reinforcing phase content on the relative density, micro-hardness, and compressive behaviour of the compacted samples along with their microstructures were investigated. The results showed that the micro-hardness and the compressive strength of the samples fabricated at 450°C increased about 70% and 50%, respectively.